Pentingnya Peran Keluarga Dalam Membentuk Identitas Dan Peran Gender Pada Anak Usia Dini - Nur Fitria, Anisa; Muthoharoh, Atika (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2024)
The role of father and mother in the family is very vital in a child's growth. They are tasked with caring for children, being children's friends, providing teaching about values and norms, especially those related to gender roles, acting as role models for children, and also as breadwinners to meet the family's economic needs. This research uses a qualitative descriptive method to explain how parents contribute to shaping the gender identity of young children (5-6 years). The research informants were parents with young children, and data was collected through observation, in-depth interviews and related documentation. The results of this research provide in-depth insight into the development of children's gender identity in the family context, as well as how the role of parents can influence this development. By the age of five, gender stereotypes begin to emerge. The results of this research provide guidance for parents in helping children achieve a healthy gender identity, by understanding the values, norms and gender roles associated with their gender.Â